Strategies for sustainable land management and poverty reduction in Uganda - Nkonya, Ephraim M.; Pender, John L.; Jagger, Pamela; Sserunkuuma, Dick; Kaizzi, Crammer; Ssali, Henry (International Food Policy Research Institute, 2004)
The government of Uganda, with help from its development partners, is designing and implementing policies and strategies to address poverty, land degradation, and declining agricultural productivity. Land degradation, especially soil erosion and depletion of soil nutrients, is widespread in Uganda and contributes to declining productivity, which in turn increases poverty. The report has four major objectives: (1) to examine the causes of land degradation in Uganda; (2) to identify the determinants of income strategies and land management decisions and their impacts on agricultural productivity, soil erosion, and household income; (3) to assess the trade-offs and complementarities among these different objectives; and (4) to analyze the soil nutrient depletion in eastern Uganda to determine the factors that influence it. -- from Text